2012
DOI: 10.1186/1475-2859-11-71
|View full text |Cite
|
Sign up to set email alerts
|

Single cell oil of oleaginous fungi from the tropical mangrove wetlands as a potential feedstock for biodiesel

Abstract: Background: Single cell oils (SCOs) accumulated by oleaginous fungi have emerged as a potential alternative feedstock for biodiesel production. Though fungi from mangrove ecosystem have been reported for production of several lignocellulolytic enzymes, they remain unexplored for their SCO producing ability. Thus, these oleaginous fungi from the mangrove ecosystem could be suitable candidates for production of SCOs from lignocellulosic biomass. The accumulation of lipids being species specific, strain selection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 43 publications
1
60
0
Order By: Relevance
“…Twenty-one fungal cultures were isolated from mangrove wetlands and maintained on Czapek's Dox agar (CDA) as described by Khot et al (2012 Li et al (2011). Media components were then added to the hydrolysate and filter-sterilized into 500-ml conical flask prior to inoculation.…”
Section: Strains and Growth Conditionsmentioning
confidence: 99%
“…Twenty-one fungal cultures were isolated from mangrove wetlands and maintained on Czapek's Dox agar (CDA) as described by Khot et al (2012 Li et al (2011). Media components were then added to the hydrolysate and filter-sterilized into 500-ml conical flask prior to inoculation.…”
Section: Strains and Growth Conditionsmentioning
confidence: 99%
“…It is eco-friendly, non-toxic, bio-degradable, stable, reduces the level of potential or probable carcinogens, and has a favorable emission profile [3]. It is produced from an array of inexpensive and renewable raw materials such as lignocellulosic biomass [4], plant seed oils [5,6], waste glycerol [7], corn cob waste liquor [8], wheat straw [9], and agro-residues [10]. Utilization of these by-products will make an important contribution in the reduction of overall production costs of biodiesel in the global market which is the major reason for researchers focusing their attention on oleaginous fungi [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Authors proposed a mathematical model to simulate the consumption of sugar and nitrogen, the fat-free biomass formation, and the accumulation of lipids (Economou et al 2011). Khot et al (2012) isolated fungi of tropical mangrove wetlands, but only five out of 14 showed lipid accumulation above 20 % dry cell biomass. Fungi from this ecosystem were also used for the production of lignocellulosic enzymes.…”
Section: Filamentous Fungimentioning
confidence: 99%